Play with trick. Art therapy workshop in the children attention centre of Aldeas Infantiles in Granada - Manuela Avilés Martos; Elizaberta López Pérez (Arteterapia)
This is the experience of an art therapy workshop conducted in a Day Care Center for Children of Aldeas Infantiles SOS Granada. The title, play with trick, tries to refer to the conclusion of one of the participants in the workshop, which spontaneously arrived to the conclusion of the "trick" of art therapy: which is the result of the personal reflection that has to be discovered by themselfs with implicit learning.